perbandingan hasil koreksi mata sipit menggunakan dua bulu mata ditambah dengan scotch tape dan tiga bulu mata palsu untun rias pengantin bridal - khumairah khumairah (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
The purpose of the research to knows comparison of slit eye correction results using two lashes with the addition of scotch tape and three lashes for bridal makeup. This research method uses quasi-experimental methods with Non equivalent control group design. Sampling using purposive sampling technique. The analysis shows that there are differences in the level of neatness in the technique of using two lashes with scotch tape and the use of three lashes for bridal makeup (p=0,035). Where the highest average value was found using three Eyelashes (X2) which is equal to 2.47. There are no significant differences in eye impression indicators seen in the technique of using two lashes with scotch tape and the use of three lashes for bridal makeup (p=0,035). However, the highest average value was found using three Eyelashes (X2) which was equal to 2.67. There are significant differences in eye impression indicators on the technique of using two lashes with the addition of scotch tape and the use of three lashes for bridal makeup (p=0,010). Where the highest average value was found using three Eyelashes (X2) which is equal to 2.93. the best result bridal makeup is using three eyelashes technique for more perfect .